Performance Comparison of PID and Fuzzy Controllers in Distributed MPPT - Chandani Sharma; Anamika Jain (Institute of Advanced Engineering and Science, 2015)
With an increase of Green Technology applications, Photovoltaic have emerged as the most appropriate solution for electricity generation purposes. However, due to variable temperature and irradiance, under the partial or shaded conditions Maximum Power Point Tracking is needed to determine highest efficiency of the system. The paper describes dynamic modeling and control of variable temperature and irradiance on solar panel in SIMULINK-MATLAB environment. The implementation of Buck Converter is used for power switching and impedance matching on connecting the panel to the load. The effectiveness of the model, with enhanced efficiency through voltage stabilization, is performed using Proportional-Integral-Derivative and Fuzzy-Logic-Controllers. A comparative study is made for PID and FLC on the basis of outputs to deal with online set point variations. FLC gives closer results to Standard Test Conditions when compared with PID. The Fuzzy system developed, using tested membership functions serve as a platform for sustainable standalone and grid-based applications using distributed MPPT. With an increase of Green Technology applications, Photovoltaic have emerged as the most appropriate solution for electricity generation purposes. However, due to variable temperature and irradiance, under the partial or shaded conditions Maximum Power Point Tracking is needed to determine highest efficiency of the system. The paper describes dynamic modeling and control of variable temperature and irradiance on solar panel in SIMULINK-MATLAB environment. The implementation of Buck Converter is used for power switching and impedance matching on connecting the panel to the load. The effectiveness of the model, with enhanced efficiency through voltage stabilization, is performed using Proportional-Integral-Derivative and Fuzzy-Logic-Controllers. A comparative study is made for PID and FLC on the basis of outputs to deal with online set point variations. FLC gives closer results to Standard Test Conditions when compared with PID. The Fuzzy system developed, using tested membership functions serve as a platform for sustainable standalone and grid-based applications using distributed MPPT.